HUKUM PERKAWINAN PASANGAN BEDA AGAMA DI INDONESIA - Sofiya Nuryanti; Muh. Jufri Ahmad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This study discusses mixed marriages between those of different nationalities, different ethnicities, races or religions, which often occurs in Indonesia, namely interfaith marriages. This has become a controversial issue in Indonesia, where the rules regarding marriage are not clear and more and more interfaith marriage practices occur, so research is needed. The type of research used in this research is normative legal research by conducting research on legal norms that apply in Indonesia related to the proposed legal issues. It can be concluded that marriages to interfaith couples often occur and cause problems in the administration due to the absence of clear rules and set out as a prohibition, although in Indonesia marriage to interfaith couples is not justified, but the Population Administration Law provides an opportunity but the civil registry office does not. record interfaith marriages. So it is necessary to clarify the laws governing it so that the Indonesian people get legal certainty regarding this interfaith marriage